Ten-Year Follow-Up of a Fragment Reattachment to an Anterior Tooth: A Conservative Approach - Luiz Mendes; Laisa Laxe; Leandro Passos (Case Reports in Dentistry)
This report describes the 10-year follow-up data of a patient who underwent fragment reattachment to the maxillary central incisor after coronal fracture with pulp exposure as well as the procedures followed for functional and esthetic adjustments. A 9-year-old female patient presented at the clinic of dentistry at the State University of Rio de Janeiro with a coronal fracture and pulp exposure of the right maxillary central incisor that had occurred immediately after an accident. The intact tooth fragment was recovered at the accident site and stored in milk. The treatment plan followed was to perform direct pulp capping and tooth fragment reattachment. When the patient was 14 years old, adhesion between fragment and remaining tooth was lost, and fragment reattachment was performed. Five years later, the same tooth presented clinical discoloration and absence of sensitivity during pulp vitality tests. Subsequently, a new treatment plan was formulated, which included endodontic treatment, followed by nonvital tooth bleaching and light-cured composite resin restoration. An esthetic and natural-looking restoration was achieved. Tooth fragment reattachment is not a temporary restorative technique and requires functional and esthetic adjustments over time to maintain the biomimetic characteristics of traumatized anterior teeth and predictable outcomes.